2021
DOI: 10.35633/inmateh-63-30
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Field Efficiency of Sugarcane Harvesters

Abstract: Field efficiency is a main factor for obtaining high productivity of agricultural machinery. The aim of this paper was to determine the field efficiency of KTP 2M and CASE IH 8000 sugarcane harvester machines, working with different lengths of cutting fronts. The research was carried out in the Panchito Gómez Toro area of production, belonging to Sugar Enterprise, Villa Clara, during February and March 2020. The main movement times of the harvester inside the field was obtained by stop watch, as well as the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…In comparison, reported losses from remaining stumps in Brazil were around 0.05 t/ha, making the losses in Tailand approximately 44.2 times higher than those in Brazil [22]. Unlike Brazil and Australia, where sugarcane plots are well prepared for mechanized harvesting, leading to minimal losses from basal cutting, sugarcane cultural practices in Tailand need improvement, especially in areas such as earthing-up operations and rock clearing in sugarcane felds [20]. By adequately preparing sugarcane felds in Tailand, the basal cutting of harvesters could be performed closer to the bases of sugarcane stumps, resulting in reduced cane losses [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, reported losses from remaining stumps in Brazil were around 0.05 t/ha, making the losses in Tailand approximately 44.2 times higher than those in Brazil [22]. Unlike Brazil and Australia, where sugarcane plots are well prepared for mechanized harvesting, leading to minimal losses from basal cutting, sugarcane cultural practices in Tailand need improvement, especially in areas such as earthing-up operations and rock clearing in sugarcane felds [20]. By adequately preparing sugarcane felds in Tailand, the basal cutting of harvesters could be performed closer to the bases of sugarcane stumps, resulting in reduced cane losses [22].…”
Section: Discussionmentioning
confidence: 99%
“…Te fndings also indicated that many farmers did not adequately prepare their sugarcane farms for the use of harvesters, which can markedly afect harvesting efciency. Insufcient farm preparation can lead to increased working time for harvesters in the feld without a corresponding increase in the working area, resulting in decreased efciency [20].…”
Section: Discussionmentioning
confidence: 99%